PEMBERDAYAAN BERBASIS MASJID DALAM PERSPEKTIF DAKWAH - Mardan Mahmuda; Sarwan Sarwan (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Speaking of mosque-based empowerment, then in the perspective of da'wah can be ascertained that the empowerment activity in question is Islamic empowerment and makes the mosque the center of its activities to realize the happiness of Islamic society in a secular and ukhrawi. Besides, the activity can restore the function of the mosque which should not only be a place of worship but also serve as a place of social activities such as empowerment activities. This article was compiled using qualitative methods through a literary study approach. Literature studies are conducted by collecting, reading, and analyzing various literature or references such as books, scientific journals, and various other scientific works related to mosque-based empowerment, da'wah-based empowerment, empowerment preaching, and so on. This article is about; definition of empowerment and da'wah, the nature and function of the mosque, the nature of empowerment and da'wah and discuss in detail mosque-based empowerment from the perspective of da'wah. This study is expected to be a contribution to empowerment agencies especially for scientists and da'wah practitioners who want to realize the welfare of the Islamic community of the world and the afterlife. As a reference for empowerment institutions, religious institutions, and other social institutions to empower the Islamic community to the maximum and sustainable.